Mathematics teacher learning in the context of South African outcomes-based education reforms - Maoto, Rose Satsope (Curtin University, 2003)
The new South African national curriculum for the twenty first century adopted an outcomes-based education approach. The new curriculum represents a crucial shift in emphasis from learners concentrating on formal and procedural mathematics (with an absence of meaning) to learners making meaning of mathematics and becoming flexible mathematical thinkers, with problem solving and mathematics investigations as central focus. This study reports on an action research collaboration between two teachers and myself, a university mathematics educator. It was conducted over a period of three years. The main purpose of our collaboration, and this thesis, was to explore mathematics teacher learning in the context of the OBE-based reforms. The data were gathered through questioning, journal keeping by the two teachers and my participant observations. Using the two teachers’ reflective writings and field notes I analysed the data in two stages - narrative analysis and analysis of narratives. What emerged from the study were several issues clustered around three characteristics of teacher learning - teacher learning as situated, teacher learning as social and teacher learning as distributed. These three overlapping characteristics of teacher learning were used as heuristic devices or convenient organisers for the description, analysis and discussion of the issues that emerged. This study revealed several overarching propositions that may have applicability beyond its boundaries. The first proposition is that teachers reflect on and revise their personal practical knowledge if exposed to learning experiences that encourage them to attach meaning to and make sense of the underlying concepts of new curriculum reforms. The second proposition is that interactions with literature improve the quality of teacher learning.The third proposition is that teachers are motivated to experiment with new ideas if they observe these ideas being modelled in practice. The fourth proposition is that teachers develop positive perceptions about learning if the expectations of multiple stakeholders (both in their classrooms and beyond the classrooms) are not contradictory. The fifth proposition is that teachers’ listening to learners’ thinking opens opportunities for explorations. The sixth proposition is that I teachers respond to learners’ learning by being more curious about classroom discussions. The seventh proposition is that teachers who play an active role in collaborative working relationships are more likely to revise their pedagogy. The eighth proposition is that true collaborative relationships take time. The last proposition is teachers who are supported are more likely to distribute their knowledge and learning. Some implications of this study are also highlighted in the last chapter.